The Contribution Of ZIS Funds In Strenggthening Rural Infrastructure - Ridwan, Murtadho; Andriyanto, Irsad (ZISWAF, 2018)
The utilization of zakat funds has developed from its origin as stated in the al Quran and law no. 23 of 2011 that categorized the recipients into 8 groups (asnaf). This study aimed to analyze the reason of zakat funds utilization for infrastructure development and how much their contribution to rural infrastructure. By taking place in one of the villages in Demak district, the researcher get data through an interview with key informants, observation, and tracking of documents on the use of zakat funds of the existing zakat collection institutions. This was a qualitative study that used miles and hubberman model to analyze the data by four steps analysis. The results indicated that the reason for using zakat funds for infrastructure development is the opinion that categorized the committee of infrastructure development into gharim because of its debt. Moreover, zakat funds contribute to the construction of mosques, educational facilities, as well as a graveyard. Finally, the results has proven the effectiveness of zakat particularly in fostering prosperity and poverty alleviation.